Active control of flow-induced vibrations on slider in hard disk drives : experimental demonstration - Min, Hequn (2013)
This paper presents an experimental demonstration on the active control of flow-induced vibrations on a head gimbals assembly (HGA) bearing a slider in a hard disk drive (HDD). The feedback control closed-loop consisted of a laser Doppler vibrometer (LDV), a narrowband frequency filter, a signal conditioner, an in-house made phase shifter, and a piezoelectric disk mounted on the inner surface of the HDD cover. The HGA vibrations detected by the LDV were used as feedback error signals, and the signals were then phase shifted and amplified to drive the piezoelectric disk to generate feedback acoustic pressure around the HGA. The phase shift and gain of the feedback loop were adjusted such that the HGA vibrations were reduced. The experiments of active control have been conducted on five principal peaks in the HGA off-plate vibration spectrum, around 1256, 1428, 2141, 2519, and 3469 Hz, respectively. The results show that reduction of the HGA vibrations can be achieved on all these principal peaks, with a maximum suppression of 16 dB on the peak around 1428 Hz. It is also observed that simultaneous reduction can take place among these peaks when the narrowband feedback control is focused only on one of them.